Spiking neuromorphic chip learns entangled quantum states - Czischek, Stefanie; Baumbach, Andreas; Billaudelle, Sebastian; Cramer, Benjamin; Kades, Lukas; Pawlowski, Jan M.; Oberthaler, Markus K.; Schemmel, Johannes; Petrovici, Mihai A.; Gasenzer, Thomas; Gärttner, Martin (SciPost physics, 2022)
SciPost Journals Publication Detail SciPost Phys. 12, 039 (2022) Spiking neuromorphic chip learns entangled quantum states
Gesehen am 13.07.2022